2014
DOI: 10.1515/multi-2014-0007
|View full text |Cite
|
Sign up to set email alerts
|

‘And then we summarise in English for the others’: The lived experience of the multilingual workplace

Abstract: In multinational corporate companies, multilingualism is often a daily reality for employees and the negotiation of language practices for work and social purposes, a routine. Despite the role of English as a lingua franca, the linguistic ecology of modern workplaces is dynamic, rich and diverse. While English is often used for communication between a company’s headquarters and its subsidiaries, language choice is dynamically negotiated between the interactants in informal meetings and everyday interactions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 0 publications
1
35
0
Order By: Relevance
“…There is a little French and German, with which they cannot fully adapt to the language demands of their foreign clients. These results are in agreement with findings of Angouri and Miglbauer (2014). In general employees tend to prioritize English, even if they admit that other languages also play an important role.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There is a little French and German, with which they cannot fully adapt to the language demands of their foreign clients. These results are in agreement with findings of Angouri and Miglbauer (2014). In general employees tend to prioritize English, even if they admit that other languages also play an important role.…”
Section: Discussionsupporting
confidence: 92%
“…These more vague or ambiguous policies are in line with a call for a ''flexible'' policy and language practices based on a ''what works'' approach. In another study, Angouri and Miglbauer (2014) interviewed 40 employees in twelve European companies that have English as the corporate language. Their aim was to analyze employees' perceptions of the role of languages in their daily work life.…”
Section: Introductionmentioning
confidence: 99%
“…Not in the least because a policy of multilingualism alone would be too expensive and goes against the wish to control and to coordinate information flows within the company. Other studies have found that in many MNCs multilingualism exists in combination with ELF as the official corporate language in that for the international workforce negotiating language practices is a daily routine (Angouri and Miglbauer 2014).…”
Section: Limitations and Further Researchmentioning
confidence: 99%
“…While local cultures gain value as a source of profit, local languages have little currency. What dominates is English, as the lingua franca of globalised tourism -and the globalised workplace (Angouri and Miglbauer 2014). If Workaway envisions multilingualism as part of a cosmopolitan subjectivity, as a key to promoting cultural understanding throughout the world, in the tourist resort languages are valued as one of the skills among others that are needed for running a business.…”
Section: Discussionmentioning
confidence: 99%